2004
DOI: 10.7326/0003-4819-140-5-200403020-00009
|View full text |Cite
|
Sign up to set email alerts
|

Excess Body Weight Is Not Independently Associated with Outcome in Mechanically Ventilated Patients with Acute Lung Injury

Abstract: After risk adjustment, overweight and obese patients with acute lung injury have outcomes similar to those of patients with normal BMI. The lack of interaction between ventilator protocol assignment and BMI suggests that patients with normal, overweight, or obese BMI benefit from lower tidal volume ventilation for acute lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
114
4
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 30 publications
5
114
4
5
Order By: Relevance
“…This is supported by prior studies in ALI/ARDS that showed either a trend for a protective mortality effect by obesity (3) or a significantly lower mortality in obese patients (47). However, our study differed from others that reported either a higher ICU mortality (48) or no association with 28-day mortality with obesity (49). This may be explained by differences in sample size, study design, or patient characteristics.…”
Section: Discussioncontrasting
confidence: 56%
“…This is supported by prior studies in ALI/ARDS that showed either a trend for a protective mortality effect by obesity (3) or a significantly lower mortality in obese patients (47). However, our study differed from others that reported either a higher ICU mortality (48) or no association with 28-day mortality with obesity (49). This may be explained by differences in sample size, study design, or patient characteristics.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous reports investigating the association between BMI and mortality in mechanically ventilated patients show inconsistent results. [16][17][18][19][20] These results must be interpreted with caution. A comparison of non-obese and morbidly obese mechanically ventilated subjects showed similar mortality in both groups.…”
Section: Discussionmentioning
confidence: 98%
“…Because underweight subjects have been reported to have a higher mortality than normal-weight subjects in the ICU, 15,24-29 combining underweight and normal-weight patients into one category may bias the results. Another report included only 807 subjects, 19 which might not be a sufficient sample size to detect differences in outcomes between different BMI categories. Four of these reports 16,17,19,20 restricted the study population to subjects with acute lung injury and ARDS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations